2013
DOI: 10.1007/s00417-013-2289-4
|View full text |Cite
|
Sign up to set email alerts
|

One-year results of reduced fluence photodynamic therapy for central serous chorioretinopathy: the outer nuclear layer thickness is associated with visual prognosis

Abstract: RFPDT appears to be an effective treatment method for CSC. ONL thickness is an important visual predictive factor of RFPDT for CSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
4
17
1
Order By: Relevance
“…CSR as an RPE disease 8 and IZ as the representation of the region of the distal portion of the cone's outer segment which indicated contact cylinder with the apposed RPE cell body is expected that the regulation of the disease can be translated in more IZ presence by SML treatment. 21 ONL has been described as a biomarker of better prognosis in CSR [22][23][24][25] and 532-SML marginally increased the ONL thickness in our study, without statistically significant variation. Treatment was applied subfoveally if necessary.…”
Section: Discussionsupporting
confidence: 42%
“…CSR as an RPE disease 8 and IZ as the representation of the region of the distal portion of the cone's outer segment which indicated contact cylinder with the apposed RPE cell body is expected that the regulation of the disease can be translated in more IZ presence by SML treatment. 21 ONL has been described as a biomarker of better prognosis in CSR [22][23][24][25] and 532-SML marginally increased the ONL thickness in our study, without statistically significant variation. Treatment was applied subfoveally if necessary.…”
Section: Discussionsupporting
confidence: 42%
“…The follow-up period after RFPDT treatment reported by Goto et al8 is short (only 3 months), but the two patients in our study were followed for 6 months to 1 year, and no recurrence of PED was observed. Reducing PDT energy is believed to decrease the incidence of persistent choriocapillaris hypoperfusion, pigmentary changes of retinal pigment epithelium, choroidal atrophy, and secondary choroidal neovascularization as PDT-induced adverse events,7,9 and, if an equivalent therapeutic effect can be obtained, the lower-fluence PDT used in our method of treatment may make it superior to that reported by Goto et al8…”
Section: Discussionmentioning
confidence: 79%
“…After intravenous administration of the same dose of verteporfin as used in standard-fluence PDT (6 mg/m 2 of body surface intravenously for 10 minutes), RFPDT was carried out using the VISULAS 690S PDT system (Carl Zeiss Meditec AG, Jena, Germany) with 83-second exposure, as for standard-fluence PDT, and energy per surface area of 25 J/cm 2 . The RFPDT laser spot size was determined by the same method previously reported for CSC;9 namely, the spot size was set to cover hyperfluorescent areas (including the whole PED area) identified from mid-phase or late-phase ICGA images. A Cirrus HD-OCT system (Carl Zeiss Meditec) was used for optical coherence tomography (OCT) using protocols of macular cube scan and HD 5-line raster scan.…”
Section: Methodsmentioning
confidence: 99%
“…The morphologic change in ONL is associated with visual prognosis in patients with DME. 36,37 Similarly, ONL integrity is crucial for visual prognosis in other types of retinal diseases, such as central serous chorioretinopathy 38 and AMD. 39 Therefore, the current data may indicate that blockage of VAP-1/SSAO is beneficial to avoid visual function loss after laser photocoagulation.…”
Section: Discussionmentioning
confidence: 99%